Colorado water, August/September 2007 - Colorado Water Resources Research Institute, author (Colorado State University. Libraries, 2007)
Newsletter of the Water Center of Colorado State University.
The scope of the newsletter is devoted to enhancing communication between Colorado water users and managers and faculty at the research universities in the state.
Keywords: Water resources development -- Colorado; Water use -- Colorado; Water-supply -- Colorado; Water-supply -- Management -- Colorado